The effect of reviewer's review volumes on online consumer reviews' perceived usefulness: An event-related potential study. (25th September 2021) - Liu, Jianhua; Mo, Zan; Gao, Hongming
Highlights: Reviewers' review volumes positively influence the perceived usefulness. The high review volume condition led to higher perceived useful rate. The high review volume condition induced less negative N2 and more positive LPP. Abstract: What is the most useful online consumer review? Consumers face the challenge of identifying useful online consumer reviews, some of which might have been manipulated by retailers. Reviewer's review volumes is the past behavior of a reviewer which is one of the most important cues of the reviewer expertise. While reviewer cues are receiving increasing attention, the effect of reviewer's review volumes on the perceived usefulness of online consumer review remains under-explored. This research explored the underlying neural mechanism of reviewer's review volumes on the perceived usefulness of online consumer reviews by applying the event-related potentials (ERPs) approach. Behaviorally, a higher perceived usefulness rate and reduced reaction time were observed for the high-review-volume condition compared to the low-review-volume condition, indicating that the high-review-volume condition was more desirable to the participants. At the neural level, the high-review-volume condition elicited an attenuated N2 and an increased LPP compared with the low-review volume condition, suggesting a more positive evaluation of the high-review volume condition. These results showed the positive impact of the reviewer's review volumes on the perceived usefulness of online consumer reviews and its potential neural substrates.